The Effectiveness of The ASN Mobile Attendance Application (M-Pras) In Improving Work Discipline For Civil Servants At The Secretariat of The Cirebon Regency Regional People's Representative Council - Sukma Safitri, Ajeng Ayu; Wildanu, Eka; Rengganis, Annisa (ann4publisher@gmail.com, 2024)
This study aims to describe the effectiveness of the ASN presence mobile application (m-PRAS) in improving work discipline for civil servants in the Cirebon Regency DPRD Secretariat. This type of research uses descriptive research with a qualitative approach. The data collection techniques in this study used interview, observation, and documentation techniques. The informant selection technique in research uses purposive sampling techniques. The results of this study, as seen from the effectiveness indicators according to Sutrisno (2007), are as follows: First, the program's understanding of implementing attendance in the m-PRAS application can be understood well. Second, target accuracy in implementing attendance in the m-PRAS application is on target and has achieved the targets set. Third, punctuality in attendance in the m-PRAS application was carried out on time according to the predetermined schedule. Fourth, the Achievement of goals of implementing attendance in the m-PRAS application based on the Cirebon Regent's Circular Letter Number 780/457/BKPSDM, namely to improve employee discipline and performance, has not been achieved. Fifth, real change in the implementation of attendance in the m-PRAS application has had a positive impact, but there are shortcomings in the m-PRAS application, such as server errors when taking attendance. The conclusion in this study states that the implementation of attendance on the ASN attendance mobile application (m-PRAS) at the Cirebon Regency DPRD Secretariat has not been effective. In this case, the purpose of implementing the m-PRAS application to improve civil servants' discipline and performance is still low and has not been appropriately realized.